Cortical activity during motor execution, motor imagery, and imagery-based online feedback. - Miller, K.J.; Gerwin Schalk; Fetz, Eberhard E; den Nijs, Marcel; Ojemann, J G; Rao, Rajesh P N (Proc Natl Acad Sci U S A, 2010)
Imagery of motor movement plays an important role in learning of complex motor skills, from learning to serve in tennis to perfecting a pirouette in ballet. What and where are the neural substrates that underlie motor imagery-based learning? We measured electrocorticographic cortical surface potentials in eight human subjects during overt action and kinesthetic imagery of the same movement, focusing on power in "high frequency" (76-100 Hz) and "low frequency" (8-32 Hz) ranges. We quantitatively establish that the spatial distribution of local neuronal population activity during motor imagery mimics the spatial distribution of activity during actual motor movement. By comparing responses to electrocortical stimulation with imagery-induced cortical surface activity, we demonstrate the role of primary motor areas in movement imagery. The magnitude of imagery-induced cortical activity change was approximately 25% of that associated with actual movement. However, when subjects learned to use this imagery to control a computer cursor in a simple feedback task, the imagery-induced activity change was significantly augmented, even exceeding that of overt movement.
Keywords: Adolescent; Adult; Biofeedback, Psychology; Cerebral Cortex; Child; Electric Stimulation; Electrocardiography; Female; Humans; Male; Middle Aged; Motor Activity; Young Adult

Non-invasive brain-computer interface system: towards its application as assistive technology. - Cincotti, F; Mattia, Donatella; Aloise, Fabio; Bufalari, Simona; Gerwin Schalk; Oriolo, Giuseppe; Cherubini, Andrea; Marciani, Maria Grazia; Babiloni, Fabio (Brain Res Bull, 2008)
The quality of life of people suffering from severe motor disabilities can benefit from the use of current assistive technology capable of ameliorating communication, house-environment management and mobility, according to the user's residual motor abilities. Brain-computer interfaces (BCIs) are systems that can translate brain activity into signals that control external devices. Thus they can represent the only technology for severely paralyzed patients to increase or maintain their communication and control options. Here we report on a pilot study in which a system was implemented and validated to allow disabled persons to improve or recover their mobility (directly or by emulation) and communication within the surrounding environment. The system is based on a software controller that offers to the user a communication interface that is matched with the individual's residual motor abilities. Patients (n=14) with severe motor disabilities due to progressive neurodegenerative disorders were trained to use the system prototype under a rehabilitation program carried out in a house-like furnished space. All users utilized regular assistive control options (e.g., microswitches or head trackers). In addition, four subjects learned to operate the system by means of a non-invasive EEG-based BCI. This system was controlled by the subjects' voluntary modulations of EEG sensorimotor rhythms recorded on the scalp; this skill was learnt even though the subjects have not had control over their limbs for a long time. We conclude that such a prototype system, which integrates several different assistive technologies including a BCI system, can potentially facilitate the translation from pre-clinical demonstrations to a clinical useful BCI.
Keywords: Activities of Daily Living; Adolescent; Adult; Brain; Child; Electroencephalography; Evoked Potentials, Motor; Female; Humans; Learning; Male; Middle Aged; Motor Skills; Muscular Dystrophy, Duchenne; Pilot Projects; Prostheses and Implants; Robotics; Self-Help Devices; Software; Spinal Muscular Atrophies of Childhood; User-Computer Interface; Volition

Unique cortical physiology associated with ipsilateral hand movements and neuroprosthetic implications. - Wisneski, Kimberly; Nicholas R Anderson; Gerwin Schalk; Smyth, Matt; Moran, D; Leuthardt, E C (Stroke, 2008)
BACKGROUND AND PURPOSE:  Brain computer interfaces (BCIs) offer little direct benefit to patients with hemispheric stroke because current platforms rely on signals derived from the contralateral motor cortex (the same region injured by the stroke). For BCIs to assist hemiparetic patients, the implant must use unaffected cortex ipsilateral to the affected limb. This requires the identification of distinct electrophysiological features from the motor cortex associated with ipsilateral hand movements. METHODS:  In this study we studied 6 patients undergoing temporary placement of intracranial electrode arrays. Electrocorticographic (ECoG) signals were recorded while the subjects engaged in specific ipsilateral or contralateral hand motor tasks. Spectral changes were identified with regards to frequency, location, and timing. RESULTS:  Ipsilateral hand movements were associated with electrophysiological changes that occur in lower frequency spectra, at distinct anatomic locations, and earlier than changes associated with contralateral hand movements. In a subset of 3 patients, features specific to ipsilateral and contralateral hand movements were used to control a cursor on a screen in real time. In ipsilateral derived control this was optimal with lower frequency spectra. CONCLUSIONS:  There are distinctive cortical electrophysiological features associated with ipsilateral movements which can be used for device control. These findings have implications for patients with hemispheric stroke because they offer a potential methodology for which a single hemisphere can be used to enhance the function of a stroke induced hemiparesis.
Keywords: Adolescent; Adult; Artificial Limbs; Bionics; Brain Mapping; Child; Dominance, Cerebral; Electroencephalography; Female; Hand; Humans; Male; Middle Aged; Motor Cortex; Movement; Paresis; Prosthesis Design; Psychomotor Performance; Stroke; User-Computer Interface; Volition